KERAJAAN DALAM ISLAMISASI NUSANTARA SEBAGAI AKAR TRADISI KEILMUAN: PASAI, ACEH, DAN MATARAM ISLAM - Aliza Nur Azizah; Dwi Ratnasari (Ta lim Jurnal Pendidikan Agama Islam dan Manajemen Pendidikan Islam, 2026)
This article examines the role of Islamic kingdoms in the Indonesian archipelago particularly Samudera Pasai, Aceh Darussalam, and Islamic Mataram in the process of Islamization and the formation of Islamic scholarly traditions, addressing the tendency of previous studies to emphasize cultural aspects and individual ulama while neglecting political power as a strategic actor. Using a qualitative method with historical-analytical and comparative approaches through the study of historical sources, academic literature, and Islamic historiography, this research analyzes the position of Islamic kingdoms in Islamization, patterns of relations between sultanates and ulama, variations in Islamization strategies, and their relevance to contemporary Islamic Religious Education. The findings show that Islamization in the Indonesian archipelago occurred in a directed and structured manner through active royal support for da‘wah, the establishment of educational institutions, and the development of a sustainable Islamic intellectual tradition. Although each kingdom adopted different strategies shaped by its socio-cultural context, all demonstrate a symbiotic relationship between religious authority and political power. This study concludes that the Islamic scholarly tradition of the Indonesian archipelago is the product of historical interactions between religion and power, which remains highly relevant for the development of integrative, contextual, and civilization oriented Islamic Religious Education